The Association Between Self-Rated Health and Functional Capacity Indicators - Josiana Maria Moreira Martinez Belmonte; Naelly Renata Saraiva Pivetta; Samila Sathler Tavares Batistoni; Anita Liberalesso Neri; Flávia Silva Arbex Borim (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVE: To evaluate self-rated health and to identify its relationship with functional capacity, objective measures of muscle strength, and mobility in a sample of community-dwelling elderly adults. METHOD: A cross-sectional, population-based study using data from the "Fragility Study on Brazilian Elderly" (Fibra) electronic database, carried out between 2008 and 2009, in which 2,558 community-dwelling elderly were recruited. The dependent variable was self-rated health compared with peers of the same age, among the elderly. The odd ratios were adjusted for sociodemographic and health variables and were estimated through multinomial logistic regression. The analyses were carried out using the program Stata 14.0. RESULTS: The average age of the elderly participants was 72.3 years old (SD ± 5.5) and 65.6% of them were women. When comparing with someone of the same age, 70.2% of the participants rated their health as better than the other's; 23.4% of them rated it as equal, and 6.4% of the elderly rated it as worse. The adjusted regression model showed that the odd ratios were more important when rating health as worse among the elderly participants who were dependent on instrumental activities (OR = 2.19; 95%CI 1.22-3.92) and had weaker grip strength (OR = 0.96; 95%CI 0.93-0.99). Better health rating showed a statistically significant difference related to speed gait (OR = 0.88; 95%CI 0.81-0.94). CONCLUSION: We found associations between the self-rated health and instrumental activities of daily living, gait velocity, and grip strength. These results reinforce functionality as an important health predictor and broaden self-rated health approachs including social comparison criteria.